2018
DOI: 10.3390/ijerph15071451
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Perceptions of Compliance with a Tobacco Control Law in Restaurants in Hanoi, Vietnam: A Cross-Sectional Study

Abstract: The Tobacco Harm Prevention Law has been promulgated in 2012 in Vietnam, prohibiting smoking in public places such as restaurants except for designated smoking areas. However, currently, evidence about Vietnamese customers’ and restaurants’ compliance with the Law is constrained. This study aimed to explore customers’ perceptions; attitudes and practices towards the compliance with tobacco control regulations in the restaurants in Hanoi, Vietnam. A cross-sectional study was performed in October 2015 with 1746 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The remaining 16 full-text publications were evaluated for eligibility and only 7 of these met the eligible research were satisfactory. 12 - 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 16 full-text publications were evaluated for eligibility and only 7 of these met the eligible research were satisfactory. 12 - 18 …”
Section: Resultsmentioning
confidence: 99%
“…The study region also varied, with 6 research investigating both urban and rural areas, 12 - 15 ,17,18 while the other 1 study did not offer this figure. 16 Three surveys utilized a stratified multistage random sampling method to recruit participants and gather demographic data, 12 , 13 , 17 while 2 used convenience sampling, 14 , 18 2 did not specify particular sampling techniques. 15 , 16 Three researches shown both males and females in their analyses, 12 , 13 , 17 100% of participants were pregnant female at hospitals among 3 researches 14 , 15 , 18 , 1 study has not yet provided a sex ratios among non-smokers.…”
Section: Resultsmentioning
confidence: 99%
“…19 Our findings are also in line with a study in another province in Vietnam in 2015, which reported that 6.8% of people who had visited food facilities within 30 days prior to the interview noticed tobacco marketing at the restaurants. 20 Although the Law on Tobacco Control requires restaurants and hotels to have "no-smoking signs" in the public areas, this simple regulation was not well complied with, as only 27.7% of hotel reception areas, 16.4% of hotel lobbies, and 10.6% of restaurant dining rooms had these signs before the intervention. The study in Indonesia reported a similar trend; "no-smoking signs" were found in only 11% of hotels and 18% of restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…19 Our findings are also in line with a study in another province in Vietnam in 2015, which reported that 6.8% of people who had visited food facilities within 30 days prior to the interview noticed tobacco marketing at the restaurants. 20…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of the problem is dealing with lack of public awareness. In many LMICs, public awareness about the dangers of secondhand smoke has been found to be low resulting in lower levels of compliance (Ahuja et al, 2018;Dang et al, 2018;Nyi Latt et al, 2018;Robertson et al, 2018). A related problem is the lack of no-smoking and other educational signage.…”
Section: Introductionmentioning
confidence: 99%